Impementasi Gaya Kepemimpinan dalam Pengelolaan Manajemen di Organisasi BMT - Khairan, Khairan; Nasrudin, Nasrudin; Sodiq, Ahmad (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
The passage describes Baitul Maal wat Tamwil (BMT) as an Islamic financial institution focused on fostering economic growth, particularly within the micro, small, and medium enterprises (MSMEs) sector. It emphasizes that the success of BMTs largely depends on the leadership style employed by their leaders, who must blend Islamic principles with modern management practices to establish efficient and effective organizations.The article seeks to examine the application of leadership styles in managing BMT NUsantara UMAT MANDIRI Kalidawir Tulungagung. It explores how the leaders of this institution integrate Islamic values, human resource management, and organizational goals, creating a balanced approach to achieving sustainable success.